1984
DOI: 10.1111/j.1600-0722.1984.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the oral mucosa in 200 consecutive patients with psoriasis

Abstract: Hietanen J, Salo OP, Kanerva L, Juvakoski T: Study of the oral mucosa in 200 consecutive patients with psoriasis. Scand J Dent Res 1984; 92: 50-4.Abstract -The oral cavities of 200 consecutive psoriasis patients, most of them with widespread disease on the skin, were examined (man/woman ratio 1.63:1, mean age ofthe patients 43.7 yr). The average duration ofthe disease at time of examination was 15.8 yr. When questioned, 16% of the patients reported changes in the joints, which, according to them, had been veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 5 publications
6
47
1
3
Order By: Relevance
“…Although a proportional clinical correlation between the degree of severity (PASI average 17) of skin lesion and the frequency of geographic tongue could be seen as reported in the literature (10), we did not correlate cutaneous PASI with severity level of mucosal lesions. The severity score for the oral mucosa was performed during the clinical visit via photographic evaluation and the OPASI was also calculated.…”
Section: Methodssupporting
confidence: 45%
See 2 more Smart Citations
“…Although a proportional clinical correlation between the degree of severity (PASI average 17) of skin lesion and the frequency of geographic tongue could be seen as reported in the literature (10), we did not correlate cutaneous PASI with severity level of mucosal lesions. The severity score for the oral mucosa was performed during the clinical visit via photographic evaluation and the OPASI was also calculated.…”
Section: Methodssupporting
confidence: 45%
“…Hernandez Perez and collaborators observed that the frequency of geographic tongue and fissured tongue is higher in affected psoriatic patients (13) (16) show a high incidence of geographic tongue and fissured tongue in patients with psoriasis. In addition, Hietaten (17), detected the presence of angular cheilitis in patients with psoriasis. However, epidemiological studies indicate that the frequency of angular cheilitis is similar in the normal population (3.8%) because of the variable aetiology of this condition (full denture irritation, lack of iron or vitamin B complex , candidiasis, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their link with psoriasis remains unproven [7]. Their histologic features are similar to those of a cutaneous psoriasis [3,9,[13][14][15], but the histological distinction between psoriasis and isolated geographic/fissurated tongue cannot be made [11].…”
Section: Fig 4 Aspect Histologique De La L茅sion (Grossissement Moyementioning
confidence: 99%
“…Oral psoriasis is a rare entity and remains a subject of controversy [3,4]. In this paper, we report a case of oral psoriasis revealed by a geographic stomatitis.…”
mentioning
confidence: 96%